PENGEMBANGAN ENSIKLOPEDIA DIGITAL PADA MATERI KEKAYAAN BUDAYA INDONESIA - Siti Habibah; Drs. Dadang Kurnia, M.Pd.; Rukmini Handayani, M.Pd. (STKIP Subang, 2025)
This study aims to develop products and determine the feasibility of digitalencyclopedia on the material of Indonesia's cultural wealth. The method used inthis research is a research and development method known as Research andDevelopment with the ADDIE model (Analyze, Design, Development,Implementation, and Evaluation). The research begins with analyzing the needs ofstudents, then making a digital encyclopedia design of Indonesia's cultural wealth,then conducting expert validation and product revision. The results of the researchfrom the validation of media experts 93%, language experts 94% and materialexperts 97.3% showed that the digital encyclopedia was very feasible to use withan average percentage of 94.7%. At the implementation stage, 22 students gave avery good response to the digital encyclopedia used with an average percentageof 99.27% which means it is very feasible to use. Therefore, it can be concludedthat the development of a digital encyclopedia on the material of Indonesia'scultural wealth at Muhammadiyah Elementary School in phase B at the end of theeven semester of 2023/2024 is very feasible to use during the learning process.